SARS-COV-2 INFECTION AND THYROID DISEASES - Özlem Çelik (İstanbul Tıp Fakültesi Dergisi)
The severe acute respiratory syndrome-coronavirus-2 (SARSCoV-2) virus, was identified as the cause of a pandemic of respiratory illness in Wuhan, China one year ago. The Coronavirus disease 2019 (COVID-19), may cause mild disease with nonspecific signs and symptoms such as fever, cough, myalgia, and fatigue, or severe pneumonia with respiratory failure and sepsis. However, endocrinological manifestations are yet to be established, in patients with COVID-19. The effect of COVID-19 on thyroid function is unknown at this time. Evidence support that patients with COVID-19 who are followed up in intensive care units may develop thyroid dysfunction as a non-thyroidal illness syndrome. Until now, twenty-two cases with subacute thyroiditis and five cases with Graves’ Diseases potentially associated with SARS-CoV-2 infection have been reported in literature. Physicians should be aware of possible relationships between thyroid dysfunction and COVID-19. This study aimed to review thyroid dysfunction in patients with COVID-19, and to overview thyroid diseases that are probably related to COVID-19.